PENGARUH SELF EFFICACY DAN KEPERCAYAAN GURU PADA KEPALA SEKOLAH TERHADAP PENOLAKAN PERUBAHAN (RESISTANCE TO CHANGE) KURIKULUM 2013 PADA GURU DI SMA 1 TANJUNGSARI - , Eliyan Giri Waluyo, Prof. Djamaludin Ancok, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research on the effect of self efficacy and teachersâ trust towards the principal on resistance to change of 2013 curriculum for teachers at SMA 1 Tanjungsari aims to : 1. evaluate the effect of teacher selfefficacy on resistance to change of 2013 curriculum for teachers at SMA 1 Tanjungsari. 2. test the effect of teachers trust towards principalon resistance to change of 2013 curriculum for teachers at SMA 1 Tanjungsari .The hypotheses can be formulated as follows: 1. Self efficacy has negative effect on resistance to change of 2013 curriculum for teachers at SMA 1 Tanjungsari. 2. Teacherâs trust towards the principal has negative effect on resistance to change of 2013 curriculum for teachers at SMA 1 Tanjungsari. The research population is teachers of SMA 1 Tanjungsari by the respondents include all teachers who totaled 42 people, data retrieval is done by using a standardized questionnaire that already. Research analysis using multiple regression analysis. The conclusion derived from this research are: 1. Selfefficacy negatively affect resistance to change of2013 curriculum for teachers at SMA 1 Tanjungsari. 2. Teachersâ trust towards principal negatively affects resistance to change of2013 curriculum for teachers at SMA 1 Tanjungsari.